Stylized facts on the evolution of the enterprise size distribution in India's manufacturing sector - Radhicka Kapoor (Indian Council for Research on International Economic Relations (ICRIER), 2022)
The expansion of enterprise level datasets has led to the emergence of a large body of literature on patterns of employment and job dynamics across different enterprise types. In the context of India, where MSMEs have been traditionally supported and encouraged by different policy initiatives to generate the much needed employment opportunities outside the agriculture sector, two questions merit attention. One, whether it is in fact MSMEs or large firms that have been significant contributors to employment in the manufacturing sector. And two, how their contributions have evolved over time, across states, across industries and across rural and urban areas. Combining establishment-level data from the registered/formal and informal/unincorporated manufacturing sector in India for the period between 2000-01 and 2015-16, we find that the enterprise landscape has been dominated by micro-enterprises which have accounted for approximately 90% of total enterprises for the entire time period under study. The distribution of employment, on the other hand, has been marked by a bi-modal distribution wherein a large share of employment has been concentrated in micro-enterprises followed by large enterprises. Over time, there has been an improvement in the employment distribution with the share of medium and large enterprises in total employment rising, while that of small and microenterprises has been falling. This phenomenon is observed across labour and capital intensive industries, across most states and across rural and urban areas. The overall improvement in the employment distribution towards relatively large enterprises is a positive development as these enterprises offer higher wages compared to micro and small enterprises. Amongst other factors, the shift in the employment distribution over time appears to be a consequence of the fact that there are some MSMEs which are growing and moving up the size distribution. This suggests that for policies designed to support MSMEs to be effective in employment creation, they should seek to identify transformative enterprises which have the potential to grow fast and provide them the necessary support to expand and flourish. The question of how we identify the dynamic transformative enterprises is challenging given the data constraints and requires further research.
Keywords: E24; L60; L11; L53; 330; Employment; Manufacturing; Size Distribution of Firms; SME Policy